Utilizing historical satellite data for spatiotemporal detection of disaster-related anomalies - Carcellar, Bienvenido G. III; Nagai, Masahiko (2023)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/9480/8374
Keywords: Hazard mitigation; Remote-sensing images